A Survey of Knowledge and Practice of Regenerative Endodontics Among Nigerian Dental Residents (2014)
The aim of this survey was to assess the knowledge, attitude and practice of regenerative endodontics among dental residents in selected Nigerian hospitals. A self-administered questionnaire was used for the survey. It consisted of three parts; part A asked questions about dentists profile and knowledge, part B sought the dentist’s opinion, beliefs and judgement regarding the use of RE procedures while part C consisted of questions based on clinical practice. The results shows that the majority (91.2%) have heard about REPs which was mainly through postgraduate training but 91.9% were willing to attend courses on REPs. Most (89.1%) of participants believed that stem cell banking will be useful to regenerate dental tissues, however only 42.4% claimed to have been using some type of regenerative therapy in their practice and 28.9% considered tribiotic paste and pulpal regeneration as optimal treatment for necrotic immature teeth while 36% considered CaOH +MTA+ obturation material as the best option. As a final conclusion we can say that these results reflect that dental residents are optimistic about the use of regenerative endodontic procedures; however, a need for more research and regular training was felt